2018
DOI: 10.1007/s11886-018-1071-y
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms Linking Emotion with Cardiovascular Disease

Abstract: Purpose of Review: The present review discusses brain circuits that are engaged by negative emotions and possibly linked to cardiovascular disease risk. It describes recent human brain imaging studies that relate activity in these brain circuits to emotional processes, peripheral physiology, preclinical cardiovascular disease, as well as clinical outcomes. Recent Findings: Negative emotions and the regulation of negative emotions reliably engage several brain regions that cross-sectional and longitudinal bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 112 publications
4
41
0
Order By: Relevance
“…The second important finding of this study is CAD patients with early childhood trauma experienced greater activations in areas known to be implicated with psychological-and emotion-mediated increases in cardiovascular disease risk (Kraynak et al, 2018). Specifically, the anterior cingulate cortex, hippocampus, ventral medial prefrontal cortex, and insula appear to constitute a neural network which connects limbic and cortical structures to the peripheral vasculature (Kraynak et al, 2018;Nagai et al, 2010). Presence of early childhood trauma resulted in greater left insula deactivations and severity positively correlated with left hippocampus and ventromedial prefrontal cortex activity.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The second important finding of this study is CAD patients with early childhood trauma experienced greater activations in areas known to be implicated with psychological-and emotion-mediated increases in cardiovascular disease risk (Kraynak et al, 2018). Specifically, the anterior cingulate cortex, hippocampus, ventral medial prefrontal cortex, and insula appear to constitute a neural network which connects limbic and cortical structures to the peripheral vasculature (Kraynak et al, 2018;Nagai et al, 2010). Presence of early childhood trauma resulted in greater left insula deactivations and severity positively correlated with left hippocampus and ventromedial prefrontal cortex activity.…”
Section: Discussionmentioning
confidence: 75%
“…This study showed that early childhood trauma results in altered central neurologic responses to acute mental stress in patients with CAD. Specifically, CAD patients with early childhood trauma had increased activity in brain areas involved in emotional regulation and also in areas involved in autonomic responses to stress which could contribute to worsened CAD prognosis (Kraynak et al, 2018): the bilateral insula, anterior cingulate/medial prefrontal cortex, and cerebellum. These findings help to explain the mechanisms behind the physiologic effects of early traumatic exposures observed in other studies (Otte et al, 2005;Suglia et al, 2018), and support the growing body of evidence that early traumatic exposures may result in a catastrophic effect on the body and mind that may last throughout the life of certain individuals (Felitti et al, 1998;Goodwin and Stein, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Is there a brain phenotype— a neural pattern expressed reliably by individuals —that relates to risk for atherosclerotic cardiovascular disease (CVD)? Answering this question may not only add to a brain-based and mechanistic understanding of CVD, but may also inform approaches to predict and reduce vulnerability to a leading cause of population morbidity and mortality ( Gianaros and Jennings, 2018 ; Kraynak et al., 2018a ). Existing evidence suggests that CVD risk relates to individual differences in the functionality of cortical and limbic brain systems that encode, process and orchestrate responses to affective cues and contexts ( Kraynak et al., 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…Stress reaction is the most important link during the adaptation of an organism to environmental factors (Buckner et al, 2017). But recently, the strength and number of stressful situations that can affect the condition of tissues and organs have increased (Ginty et al, 2017;Kraynak et al, 2018). A spasm of the vessels, stomach, and pancreas is observed in the case of excessively intense or inadequately long-term exposure to stress factors (Kornicka et al, 2018;Tahtacı et al, 2018).…”
Section: Introductionmentioning
confidence: 99%